Match of psychosocial risk and psychosocial care in families of a child with cancer. Issue 12 (15th September 2017) - Sint Nicolaas, S.M.; Schepers, S.A.; van den Bergh, E.M.M.; de Boer, Y.; Streng, I.; van Dijk‐Lokkart, E.M.; Grootenhuis, M.A.; Verhaak, C.M.
Abstract: Objective: The Psychosocial Assessment Tool (PAT) was developed to screen for psychosocial risk, aimed to be supportive in directing psychosocial care to families of a child with cancer. This study aimed to determine (i) the match between PAT risk score and provided psychosocial care with healthcare professionals blind to outcome of PAT assessment, and (ii) the match between PAT risk score and team risk estimation. Methods: Eighty‐three families of children with cancer from four pediatric oncology centers in the Netherlands participated (59% response rate). The PAT and team risk estimation was assessed at diagnosis (M = 40.2 days, SD = 14.1 days), and the content of provided psychosocial care in the 5‐month period thereafter resulting in basic or specialized care. Results: According to the PAT, 65% of families were defined as having low (universal), 30% medium (targeted), and 5% high (clinical) risk for developing psychosocial problems. Thirty percent of patients from universal group got basic psychosocial care, 63% got specialized care, and 7% did not get any care. Fourteen percent of the families at risk got basic care, 86% got specialized care. Team risk estimations and PAT risk scores matched with 58% of the families. Conclusions: This study showed that families at risk, based on standardized risk assessment with the PAT, received more specialized care than families without risk. However, still 14% of the families with high risks only received basic care, and 63% of the families with standard risk got specialized care. Standardized risk assessment can be used as part of comprehensive care delivery, complementing the team.